Статистический анализ и собственные колебания рабочего колеса турбокомпрессора с учетом технологических погрешностей - Жовдак, В. А.; Смирнова, Л. М. (НТУ "ХПИ", 2001)
The static stress-and-strain state and free vibrations of cyclic symmetry structure with mistiming are investigated. The paper deals with the process misnming modeling one variant on the 3D-model of the centrifugal turbocompressor firststage wheel. Comparative results of tuned and mistimed system analysis are presented.
Keywords: газоперекачивающий турбокомпрессор; нагружения; покрывной диск; вынуждающая нагрузка